2020
DOI: 10.1159/000510572
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Ganglion Cell-Inner Plexiform Layer and Optic Nerve Head Parameters with Visual Field Sensitivity in Advanced Glaucoma

Abstract: Purpose: To evaluate the associations of optical coherence tomography (OCT)-derived macular ganglion cell-inner plexiform layer thickness (mGCIPLT), circumpapillary retinal nerve fiber layer thickness (cpRNFLT), and optic nerve head (ONH) parameters with visual field (VF) sensitivity in advanced glaucoma. Methods: In this cross-sectional study, 102 eyes from 102 patients with advanced glaucoma (defined as a 24-2 VF mean deviation (MD) of ≤−12 dB) were included. mGCIPLT, cpRNFLT, and ONH parameters (including t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…In the present study, the median rim area, cup to disc ratio, and cup volume at final visit was 0.58 mm 2 , 0.82, and 0.579 mm 3 , respectively. Previous studies assessing ONH parameters in advanced glaucoma showed similar results [ 10 , 11 ]. For instance, in a study by Lavinsky et al [ 10 ], the mean rim area, cup to disc ratio, and cup volume of eyes with advanced glaucoma was 0.65 mm 2 , 0.78, and 0.50 mm 3 , respectively.…”
Section: Discussionsupporting
confidence: 69%
“…In the present study, the median rim area, cup to disc ratio, and cup volume at final visit was 0.58 mm 2 , 0.82, and 0.579 mm 3 , respectively. Previous studies assessing ONH parameters in advanced glaucoma showed similar results [ 10 , 11 ]. For instance, in a study by Lavinsky et al [ 10 ], the mean rim area, cup to disc ratio, and cup volume of eyes with advanced glaucoma was 0.65 mm 2 , 0.78, and 0.50 mm 3 , respectively.…”
Section: Discussionsupporting
confidence: 69%
“…Thus, at the advanced stage of glaucoma beyond these cutoff points, the strength of the structure-function relationship could be decreased. Hu et al48 also demonstrated a lack of correlation between peripapillary RNFL thickness and VF sensitivity in advanced glaucoma. However, of note, we observed that the global and sectoral structure-function relationships for peripapillary RNFL measurement were quite strong in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…OCT allows for the quantitative evaluation of structural parameters of the retina [19][20][21]. The posterior pole (PP) software in Spectralis SD-OCT (Heidelberg Engineering, Germany) provides the total value of retinal thickness in an automatically tilted 8 × 8 grid (with 64 macular cells or superpixels) aligned at 7 degrees, which is the more common disc-fovea axis inclination.…”
Section: Introductionmentioning
confidence: 99%